Essential Indonesian Reading: A Learner's Guide 2 (Revised) - Dr. Liaw, Yock Fang (Times Editions, 2005)
About the Book: This two-volume series is ideal for learners who have acquired a basic knowledge of Bahasa Indonesia but wish to master its finer points. Selected and edited by well-known scholars of Indonesia, this series not only enables learners to read newspaper and books in Bahasa Indonesia but also to understand the colourful culture and lifestyle of the people of Nusantara. "Essential Indonesian Reading: A Learner’s Guide 2" provides 106 passages carefully chosen from Indonesian dailies and leading magazines. These passages introduce formal Bahasa Indonesia, using longer articles than volume 1, and more advanced language. A new feature is comprehension-style questions, complete with suggested answers at the back of volume. This will allow you, without supervision, to strengthen your knowledge of Bahasa Indonesia, and further your understanding of the people and culture of Indonesia.